Arsenic and Lead Uptake by Vegetable Crops Grown on Historically Contaminated Orchard Soils - M. B. McBride (Applied and Environmental Soil Science)
Transfer of Pb and As into vegetables grown on orchard soils historically contaminated by Pb arsenate pesticides was measured in the greenhouse. Lettuce, carrots, green beans, and tomatoes were grown on soils containing a range of total Pb (16.5–915 mg/kg) and As (6.9–211 mg/kg) concentrations. The vegetables were acid-digested and analyzed for total Pb and As using ICP-mass spectrometry. Vegetable contamination was dependent on soil total Pb and As concentrations, pH, and vegetable species. Arsenic concentrations were the highest in lettuce and green beans, lower in carrots, and much lower in tomato fruit. Transfer of Pb into lettuce and beans was generally lower than that of As, and Pb and As were strongly excluded from tomato fruit. Soil metal concentrations as high as 400 mg/kg Pb and 100 mg/kg As produced vegetables with concentrations of Pb and As below the limits of international health standards.